Produksi dan Pendapatan Usaha Terasi di Kecamatan Bengkalis Kabupaten Bengkalis Provinsi Riau - Pepsi Irana; Hendrik; Darwis AN (JURNAL SOSIAL EKONOMI PESISIR, 2021)
This research was held in August 2019 in Bengkalis Subdistrict. Research objectives is to find out how the productions and incomes of shrimp paste bussiness in each bussiness unit. The method use is survey method. Respondents of this research are owners of shrimp paste bussiness they are 5 unit in total. Based on result of the research that this bussiness used salts and pepai-shrimps as main ingredients. The production process occur in 2 weeks approximately. There are 2 outputs of this process that first was the ready consumed shrimp paste and second was half processed shrimp paste. Bussiness unit with highest production is bussiness unit that own by bussiness owner C that have 6000kg/year as annual production and IDR44.292.000,-/year as net incomes. The lowest is bussiness unit that own by bussiness owner C that have 1.200 kg/year as annual production and IDR5.429.000,00,-/year as net incomes. Total production of shrimp paste in Bengkalis Subdistict was 16.100 kg/year. 5.700 kg in the form was half processed shrimp paste and 10.400 kg in the form was the ready consumed shrimp paste.